2022
DOI: 10.1111/pbi.13802
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequence and population genomics provide insights into chromosomal evolution and phytochemical innovation of Hippophae rhamnoides

Abstract: Plants of the Elaeagnaceae family are widely used to treat various health disorders owing to their natural phytochemicals. Seabuckthorn (Hippophae rhamnoides L.) is an economically and ecologically important species within the family with richness of biologically and pharmacologically active substances. Here, we present a chromosome-level genome assembly of seabuckthorn (http://hipp.shengxin.ren/), the first genome sequence of Elaeagnaceae, which has a total length of 849.04 Mb with scaffold N50 of 69.52 Mb an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 108 publications
1
32
0
Order By: Relevance
“…There were three collinear blocks peaks of H. tibetana were detected, and located at 0.329 ± 0.001, 0.502 ± 0.002 and 2.019 ± 0.021 after data fitting ( Figure 2B ). Combining of our present analyses and the research of H. rhamnoides genome ( Yu et al., 2022 ), indicated that there were two lineage-specific polyploidization events had occurred in the genus Hippophae , and the two rounds of polyploidization occurred within a relatively narrow timeframe ( Figure S9 ) . In addition to the core-eudicot common hexaploidization (whole genome triplication, WGT; γ event, grey arrow, Figure 2A ), two prominent peaks were identified ( Hippophae recent tetraploidization, HRT: 18.7-21.2 Ma, blue arrow; Hippophae ancient tetraploidization, HAT: 28.6-32.4 Ma, red arrow, Figure 2A ) in the K s profiles of the H. tibetana genome, but unlike most other apricot, both HRT and HAT occurred at a K s value less than 1.…”
Section: Resultssupporting
confidence: 55%
See 3 more Smart Citations
“…There were three collinear blocks peaks of H. tibetana were detected, and located at 0.329 ± 0.001, 0.502 ± 0.002 and 2.019 ± 0.021 after data fitting ( Figure 2B ). Combining of our present analyses and the research of H. rhamnoides genome ( Yu et al., 2022 ), indicated that there were two lineage-specific polyploidization events had occurred in the genus Hippophae , and the two rounds of polyploidization occurred within a relatively narrow timeframe ( Figure S9 ) . In addition to the core-eudicot common hexaploidization (whole genome triplication, WGT; γ event, grey arrow, Figure 2A ), two prominent peaks were identified ( Hippophae recent tetraploidization, HRT: 18.7-21.2 Ma, blue arrow; Hippophae ancient tetraploidization, HAT: 28.6-32.4 Ma, red arrow, Figure 2A ) in the K s profiles of the H. tibetana genome, but unlike most other apricot, both HRT and HAT occurred at a K s value less than 1.…”
Section: Resultssupporting
confidence: 55%
“…Combining De novo-, transcriptome-and homology-based predictions, 33,367 protein-coding genes were predicted from the genome overall. The number of gene models is comparable to those of other Elaeagnaceae species (Mao et al, 2021;Wu et al, 2022;Yu et al, 2022). Among all the predicted genes, 32,059 genes could be annotated to the functional database, see Table S2.…”
Section: Genome Assembly and Quality Assessmentmentioning
confidence: 66%
See 2 more Smart Citations
“…The clean reads were aligned to the genome of H. rhamnoides subsp. mongolica using HISAT2–2.0.4 [ 34 , 35 ]. The aligned reads were assembled using StringTie-1.3.4 with default parameters [ 36 ].…”
Section: Methodsmentioning
confidence: 99%